Rola i znaczenie wychowania moralnego w całokształcie procesu wychowawczego rodziny - Michał Jóźwik (Wrocławski Przegląd Teologiczny)
The research show that the main educational environment if family. It can be also the best environment provided appropriate interpersonal relationships among its members take place there, i.e. among spouses, parents and children, and vice versa. One of the basic bonds in living among people is the moral one. Family life is very similar. A family wishing to be an exemplary community must realize appropriate coexistence and supply the society with valuable members – it must live moral values and present a strong moral bond, and also raise children in such atmosphere. The aim of this article is to attempt to present the significant role of moral education in family. And also to show the leading role of family in education (including the role of parents as the first teachers), and education methods and stages of moral education in family.